The Message of The Quran Karya Muhammad Asad - Lis Safitri (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2019)
This study aimed to find methodologies of translation and interpretation of The Message of the Qur`Än and the contribution of The Message of the Qur`Än to the development of the study of the Qur`Än. This study is library research with the inferential-descriptive method using historical, linguistic, and philosophical approaches. The primary data of this research is the translation and interpretation of the Qur`Än in The Message of the Qur`Än. The study shows that the type of translation of the book is tafsiriyyah translation with grouping some verses based on the small themes in the surah (munasabah). Asad interpreted the Qur`Än using the sequence of surah (tartib mushafi), with the analytical method (tahlili) and the style of adabi ijtimaâ€™i. The sources of his interpretation include the Qur`Än itself, the Hadis, the interpretation from the earlier scholars, asbab al-nuzul, sirah, dictionaries both Arabic and English, Bible, and the contemporary scientific theories. Through his work, Asad not only presented the translation with a strong linguistic study, but also enlivened the study on the Qur`Än studies, such as muhkam-mutasyabih, nasikh-mansukh, and the stories in the Qur`Än. The Message of the Qurâ€™an has been written in the contemporary method and become one of the comprehensive English translations of the Qur`Än for Muslims today.